Analisis Elemen Hingga Terhadap Perilaku Balok Beton Bertulang Yang Diperkuat Dengan Menggunakan Metode Deep Embedment - Anwar, Muhammad; Ridwan, Ridwan; Yuniarto, Enno (Journal of Infrastructure and Construction Technology, 2023)
Bridges are infrastructure buildings that are affected by technological developments. Beam structures on bridges often experience a decrease in strength, one of which is shear strength. Sometimes the shear capacity of reinforced concrete beam structures cannot meet the requirements at this time. This can be caused by increased loads, inadequate shear provisions in the initial design and material damage due to natural factors. Reinforcement methods by means of externally bonded (EB) and near-surfaced mounted (NSM) are methods that have been carried out to overcome the decrease in shear strength in beam structures. Shear reinforcement using the EB and NSM methods in practice only relies on epoxy bonding and concrete covers, this makes it susceptible to structural failure. Reinforcement method deep embedment (DE) can be used as a suggestion as shear reinforcement in reinforced concrete beams to overcome the previous problems. Reinforcement using the DE method is shear reinforcement which is reinforced at the core of reinforced concrete beams. The aim of this research is to analyzq the behaviour of reinforced concrete beams resulting from finite element modelling using ABAQUS software. This research was carried out by embedding 20 bars vertically with a distance of 100 mm along the shear span. The results of finite element modelling with ABAQUS software show that the maximum load obtained is 28,12 kN and the maximum deflection that occurs is 14,10 mm. The final result of the beam failure model is flexural failure. This is indicated by the initial crack pattern that occurs vertically in the middle of the beam span. The crack continues to propagate towards the compression area of the beam until the beam collapses.